Measurements of background radiation levels around Indian station Bharati, during 33rd Indian Scientific Expedition to Antarctica - Bakshi, A.K.; Prajith, Rama; Chinnaesakki, S.; Pal, Rupali; Sathian, Deepa; Dhar, Ajay; Selvam, T. Palani; Sapra, B.K.; Datta, D. (My University, 2017)
A comprehensive measurement of radioactivity concentrations of the primordial radionuclides 238U, 232Th and 40K and their decay products in the soil samples collected from the sites of Indian research stations, Bharati and Maitri, at Antarctica was carried out using gamma spectrometric method. The activity concentrations in the soil samples of Bharati site were observed to be few times higher than of Maitri site. The major contributor to radioactivity content in the soil at Bharati site is 232Th radionuclide in higher concentration. The gamma radiation levels based on the measured radioactivity of soil samples were calculated using the equation given in UNSCEAR 2000. The calculated radiation levels were compared with the measured values and found to correlate reasonably well. The study could be useful for the scientists working at Antarctica especially those at Indian station to take decision to avoid areas with higher radioactivity before erecting any facility for long term experiment or use.
Keywords: Radioactivity Gamma radiation level; HPGe; TLDs; PADC; Indian station Bharati; Bharti station